Uso de um reator anaeróbio de manta de lodo e fluxo ascendente (UASB) na remoção de sulfato, DQO e das espécies metálicas níquel (NI2+), zinco (ZN2+) e cobre (CU2+) - Albuquerque, Vinicius Farias de (2009)
This work had the objective of analyze the efficiency of the use of an anaerobic upflow sludge bed reactor (UASB) inoculated with methanogenic sludge proceeding from a beer industry in a treatment of a synthetic effluent with sulfate and subsequently added with the metal ions zinc (Zn2+), nickel (Ni2+) and cooper (Cu2+). The reactor was operated with a hydraulic retention time (HRT) of 18 hours and a flow of 14,9 L/day with ethanol as electron donor. The organic loading rate (OLR) was 1,5 kgDQO/m3.d during the whole running period of the reactor. The continuous flow experiment was divided into four stages after stable conditions had been achieved. At stages 1 (DQO/SO4 2- = 2,26), 2 (DQO/SO4 2- = 1,13) e 3 (DQO/SO4 2- = 0,57) the influent was added with sulfate at different concentrations allowing the analysis of the reactor behavior under different relations DQO/SO4 2-. Finally, at the stage four the metals ions were added. The stage 1 (sulfate concentration of 500 mg/L) showed average removal efficiencies of COD and sulfate of 83,61% and 67,00%, respectively, in addiction to show that the reactor remained stable during this period. Now, in step 2 (sulfate concentration of 1000 mg/L), the reactor was undergoing a period of instability due to shock load caused by new sulfate concentration, but still showed good average removal efficiencies of COD (70%) and sulfate (62%). Step 3 (sulfate concentration of 2000 mg/L) showed that under low relations DQO/SO4 2- income ends up falling, mainly due to lack of electron donor for sulfate reduction. The average removal efficiencies of COD and sulfate were 62% and 44% respectively. In step 4, was added the metal ions, initially at a concentration of 50 mg/L, there was obtained as average removal efficiencies for Zn2+, Ni2+,and Cu2+ the following values, respectively 99.17% and 99.15% 99.90%. For the influent concentration of metal ions of 150 mg/L the average removal efficiencies of nickel, zinc and copper were 99.4%, 99.5% and 99.8%, respectively. Samples of sludge taken from different heights of the reactor were also analysed to determine the distribution of metals along the length of reactor. The overall results showed good removal efficiencies of COD and sulphate, and show removal efficiencies of initial concentrations of metal ions above 99%, demonstrating the feasibility of using biological reduction of sulfate in the treatment of effluents containing high concentrations of organic matter, sulfate and heavy metals.